A Generic Reference Architecture for Collaboratory Scientific Virtual Laboratory - Absalom, Ezugwu E; Sahalu, Junaidu B; Seyed, Buhari M; Afolayan, Obiniyi A (International journal of grid and high performance computing, 2013)
The paper presents a generic reference architecture framework for collaboratory experiment virtual laboratory. The model presented is open source driven, flexible and based on modern tools and technologies. This in effect will allow geographically remote scientists with limited internal laboratory resources, access to wealth of experimental datasets, computing facilities, and distributed hard-to-duplicate laboratory devices. The key issues discussed are architectural design and choice of technology used for creating virtual laboratory. This architecture offers great levels of flexibility, simplicity, and interoperability that are needed to allow integration between heterogeneous distributed grid resources and its clients and executors. The framework, besides theoretical modelling, will provide a road map for future research and open questions.